Differentiated Instruction in EFL Classrooms: A Systematic Review - Sapkota, Hari Prasad (Journal of Natural Language and Linguistics, 2025)
This article systematically reviews recent publications (n = 21) on Differentiated Instruction in diverse English language classrooms. Differentiated instruction (DI) plays a crucial role in meeting the needs of diverse learners, particularly in EFL settings. Employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, this review identifies four major themes related to DI strategies and research methodologies: 1. Perceptions of differentiated instruction, 2. Implementation strategies and classroom practices, 3. Effects of DI on learner outcomes, and 4. Challenges and barriers for implementation. The findings suggest that DI has positive effects on diverse learners, resulting in increased engagement, positive learning outcomes, and motivation. However, challenges also exist due to time constraints, limited resources, inadequate teacher training, and classroom management issues. Methodologically, most studies employed a mixed-methods approach, followed by qualitative methods, and the fewest used quantitative methods. The review highlights the need for teacher training, policy support, and enhanced resourcing, concluding with recommendations for additional long-term studies on DI practices to examine the lasting effects.